Biodiversity Prospecting Over Time and Under Uncertainty: A Theory of Sorts - Amit Batabyal; Peter Nijkamp (European Regional Science Association (ERSA), 2014)
Biodiversity prospecting refers to the exploration of the commercial value of genetic and biochemical resources. In this chapter, we study a drug producing pharmaceutical firm (PF) that searches for potentially useful chemicals made by wild organisms in a conservation area. This PF is able to assign quality levels to the wild organisms in the conservation area. Organism quality is a proxy for the potential usefulness of the chemicals in an organism. At each date, our PF must decide whether to search for a new wild organism with a certain quality or to produce the drug in question with an extant wild organism with its own quality. Our theoretical analysis leads to four results. First, we show that if our PF discards a wild organism with a certain quality at a point in time then it will never use this same organism at a subsequent point in time. Second, we show that if our PF uses a particular organism with its quality at a point in time then it will continue to produce the drug with the chemicals from this organism at all later points in time. Third, we show that there is a threshold level of organism quality and that our PF's optimal policy involves using (discarding) all organisms with quality above (below) this threshold. Finally, we study the impacts of increases in an exogenous income source and the discount factor on our PF's threshold quality.
Keywords: D81; D83; I12; 330; Biodiversity Prospecting; Pharmaceutical Firm; Search; Time; Uncertainty